Elastic properties of the non-mixing copper donor assisted material in friction stir welding of aluminum alloys using nanoindentation - Ojha, M.; Al-Allaq, A. H.; Mohammed, Y. S.; Bhukya, S. N.; Wu, Z.; Elmustafa, A. A. (Frontiers in Metals and Alloys, 2023)
Friction stir welding of high-strength materials such as steels is the impeded by the lack of the vast heat input needed to start the process. Contact friction is considered the most dominant source of heat generation for FSW steels which tends to cause severe wear conditions of the tool hear. To relieve the extreme wear conditions that occur on the tool heads because of FSW steels, we introduce the non-mixing Cu donor stir material to friction stir welding of aluminum alloys. The elastic properties of the Cu donor assisted friction stir welded aluminum alloys are measured using nanoindentation. The hardness and elastic modulus were measured for two regions, the base metal (BM) and the stir zone (SZ). The measurements were conducted for 20% and 60% Cu non-heat treated (NHT) and heat-treated (HT) samples. The nanomechanical properties were measured using nanoindentation with the continuous stiffness method (CSM) in depth control. The HT samples are softer than the NHT samples as expected. However, the 20% Cu NHT and HT samples depicted the same hardness at the SZ. Similar results were observed for the 60% Cu donor stir samples. It therefore concluded that the SZ is softer than the BM for the 20% and 60% Cu donor stir material as expected. The hardness of the weld at the SZ is similar to the hardness of the Al6061-T6 plate, suggesting that the Cu donor stir material did not impact the hardness properties of the Al6061-T6 plate due to the depletion of the Cu donor stir material during the welding process, an important result of the concept of the donor material. The elastic moduli of the Cu donor stir welded samples vary between 75∼85 GPa at a depth of indentation of ∼4600 nm, which are different from the elastic moduli of Cu 110 (117.2 GPa) and similar to the elastic modulus of aluminum alloys (68.9 GPa), an important outcome.